Determination of nutrients in sediments from major rivers in Batan Bay, Aklan. - Talaman, Niescee Eicene Cacdac (2014.)
Nutrients are among the major types of pollutants found in sediments and water. Under anoxic conditions, nutrients in the sediments can be released back into the water. In excess amounts, nutrients can cause algal bloom and eutrophication which leads to oxygen depletion. This study determined the concentration of nitrate-nitrite concentration, available phosphorus concentration and organic matter content in sediment samples collected from Batan Bay, Aklan. Nitrate-nitrite was determined by cadmium-copper reduction method. Phosphorus was determined based on theOlsen P Method. Organic matter content was determined by the Loss on Ignition (LOI). Results showed that the mean concentrations of nitrate-nitrite ranged from 0.02-1.30 mg/kg dry weight of sediment and for phosphorus 0.01-0.90 mg/kg dry weight of sediment. The organic matter ranged from 3.97 percent-18.13 percent. In general the highest nutrient (N and P) concentrations and OM content were detected in sediments collected from Jalo River, while highest posphorus concentration was detected in sediments from Altavas River. The nitrate-nitrite concentration showed a moderately strong correlation with OM (r2=0.706), suggesting similar sources. Phosphorus, on the other hand, showed a weak correlation with OM (r2=0.281), indicating inorganic sources phosphorus such as fertilizers and detergents. Over-all, the results indicate nutrient pllution in certain sites, thus Batan Bay need monitoring.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Batan Bay, Aklan